168k views
1 vote
Can someone substitute the problem in the picture? Please

Can someone substitute the problem in the picture? Please-example-1
User Cristan
by
5.5k points

2 Answers

3 votes
If you solve by substitution , you would get and the equation -3x-2(5x-7)=12 which if you solve becomes a -3x-10x+14=12
You than want to combine like terms , so you combine -3x and -10x and bring the other problem down.
-13x+14=12
You subtract the 14 from itself and the 12 to leave -13 with its variable alone.
Now you should have -13x=-2
You divide both sides by -13 and you’ll get x=2/13
Next step is you plug back this answer to the y=5x-7
And you’ll get y= -81/13
User Mzzx
by
5.2k points
5 votes

Next time, write down the problem.

y = 5x - 7 -3x - 2y = -12

Creative box:

(5x - 7) - (3x - 2y) = -12

5x - 3x = 2x

(2x - 7) - (2y)

y = -12

2 x -12 = -24

(2x - 7) (-24) = answer (i'm not sure if its right, because I don't know if that is how the answer was supposed to be written)

User Webthusiast
by
4.9k points